Pengembangan LKPD elektronik berbasis multipel representasi untuk peserta didik SMA pada materi larutan penyangga - Tengku Afdhaluz Zikri; Sri Handayani (Jurnal Penelitian Pendidikan IPA, 2024)
The objective of this study is to develop an electronic student worksheet that utilizes multiple representations for high school students studying buffer solutions. This electronic student worksheet was created using the 4D development methodology, which encompasses the following stages: Define, Design, Develop, and Disseminate. The electronic worksheets underwent a validation process conducted by an expert validator. Field trials have been conducted and revised by developers, resulting in a valid and practical electronic student worksheet. The research outcomes indicate that the validity assessment by material and media validators falls under the category of highly valid. The practicality test conducted on six chemistry teachers from several high schools in Pekanbaru is categorized as highly practical. The small-group trial conducted with six 12th-grade science students from SMAN 5 Pekanbaru has been categorized as highly practical. Field trial on 30 12th-grade science students from SMAN 5 Pekanbaru resulted in the category of being highly practical. The conclusion drawn is that the electronic student worksheets based on multiple representations developed with a 4-D model is valid, practical, and it can be used in chemistry education at schools.